Machine learning for image-based multi-omics analysis of leaf veins - Zhang, Yubin (Journal of experimental botany, 2023)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.